EFL STUDENTS' PERCEPTION ON THE USE OF YOUTUBE AS ONLINE LEARNING MEDIA DURING COVID-19 PANDEMIC - Alan Jaelani; Rahma Habibatullaela Ande (Journal of English Language Learning, 2022)
Abstract. YouTube is a mobile application and social network that are integrated with various platforms and other media such as blogs or presentation materials. Developing a learning community through YouTube makes students experience online learning in an interesting way. The purpose of this study was to find out students' perception in learning English through online learning during Covid-19 pandemic. The participants selected for this research were five students from one of the universities in Bogor, Indonesia. This study uses qualitative research design. The results of this study indicate that YouTube is very helpful in online learning for students and this media can be accessed during online learning because it provides many educational videos to learn English and other skills. However, some difficulties were also found in this study. YouTube is also considered to add education fees in terms of connection. Students, in addition, stated that they had problem with their connection i.e., unstable signals and the ability to understand the video. This activity aims to summarize responses on the use of YouTube as a media of online learning during Covid-19 pandemic. Keywords: YouTube, Online Learning, Students Perception